2022
DOI: 10.1002/aelm.202200121
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Memristive and Memcapacitive Effects in Droplet Interface Bilayers Using Dynamic Impedance Spectroscopy

Abstract: The underlying principles for generating intelligent behavior in living organisms are fundamentally different from those in traditional solid‐state circuits. Biomimetic neuromorphic equivalents based on biological membranes offer novel implementation of tunable plasticity and diverse mechanisms to control functionality. Here, dynamic electrochemical impedance spectroscopy (dEIS) to probe diphytanoylphosphatidylcholine (DPhPC) droplet interface bilayers (DIBs) to better understand the differences in molecular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The resultant patterns from these brain activities can then lead to changes in the connections between individual neurons, a process taking place at the cellular-membrane level, implying that biological membranes with integral ion channels play a key role . By controlling the activity of the nanoscopic pore-forming ion channels embedded in membranes, one can manipulate the membranes’ resting potential, and other membrane-associated signaling, simply by controlling the flow of ions across the cellular membrane. , In doing so, molecular interactions mediated by external stimuli, e.g., periodic AC voltage waveforms, result in synaptic activity controlling biological membranes’ plasticity, including their memory resistance (memristance) and memory capacitance (memcapacitance). , Therefore, understanding the molecular scale mechanisms underlying synaptic plasticity of membranes is of fundamental importance in gaining insights into the molecular basis of learning and memory …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant patterns from these brain activities can then lead to changes in the connections between individual neurons, a process taking place at the cellular-membrane level, implying that biological membranes with integral ion channels play a key role . By controlling the activity of the nanoscopic pore-forming ion channels embedded in membranes, one can manipulate the membranes’ resting potential, and other membrane-associated signaling, simply by controlling the flow of ions across the cellular membrane. , In doing so, molecular interactions mediated by external stimuli, e.g., periodic AC voltage waveforms, result in synaptic activity controlling biological membranes’ plasticity, including their memory resistance (memristance) and memory capacitance (memcapacitance). , Therefore, understanding the molecular scale mechanisms underlying synaptic plasticity of membranes is of fundamental importance in gaining insights into the molecular basis of learning and memory …”
Section: Discussionmentioning
confidence: 99%
“…116,117 In doing so, molecular interactions mediated by external stimuli, e.g., periodic AC voltage waveforms, 118 result in synaptic activity controlling biological membranes' plasticity, including their memory resistance (memristance) and memory capacitance (memcapacitance). 117,118 Therefore, understanding the molecular scale mechanisms underlying synaptic plasticity of membranes is of fundamental importance in gaining insights into the molecular basis of learning and memory. 119 In conclusion, synaptic plasticity of lipid membranes involves intermolecular forces between lipids and ion channels.…”
Section: Biological Fluidsmentioning
confidence: 99%
“…Due to increased disorder, POPC lateral correlations are also less intense than those of DPPC bilayers, as highlighted by the randomly-circled red intensity peaks in Figure 3 where their frequency bands range between ∼2 GHz and ∼25 GHz. Importantly, phospholipid bilayers can be externally stimulated within these frequency bands through dynamic impedance spectroscopy [57], increasing conversion efficiency of mechanical energy into electric energy. NP (r, t) (Figure 1).…”
Section: Spatiotemporal Imaging Of Collective Headgroup Dipole Motion...mentioning
confidence: 99%
“…More recently, however, employing frequency-dependent dynamical electrochemical impedance spec- troscopy (dEIS), Sacci et al discovered molecular-scale changes to the dielectric properties of DPhPC (1,2diphytanoyl-sn-glycero-3-phosphocholine) bilayers, in addition to the changes in membrane thickness and area, and capacitance that had previously been associated with memcapacitance and STP. 6 While important, STP is volatile and persists only for a few seconds, making it unsuitable for nonvolatile memory storage and learning. Recently, using the same DIB system studied by Najem et al 5 and a newly developed electrical stimulation protocol (herein called training), Scott et al 7 showed that lipid bilayers can exhibit long-term potentiation (LTP) 8 associated with substantial increases in nonvolatile energy storage.…”
Section: ■ Introductionmentioning
confidence: 99%
“…More recently, however, employing frequency-dependent dynamical electrochemical impedance spectroscopy (dEIS), Sacci et al. discovered molecular-scale changes to the dielectric properties of DPhPC (1,2-diphytanoyl- sn -glycero-3-phosphocholine) bilayers, in addition to the changes in membrane thickness and area, and capacitance that had previously been associated with memcapacitance and STP …”
Section: Introductionmentioning
confidence: 99%